A working life for people with severe mental illness - Becker, Deborah R.; Drake, Robert E., 1949- (Oxford : Oxford University Press, 2003)
Supported employment is a conceptual approach to vocational rehabilitation designed for people with developmental disabilities. The Individual Placement and Support (IPS) method described within utilizes the concept, but modifies it for the severely mentally ill.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Vocational rehabilitation